First case of neurognathostomiasis in Taiwan—A Thai laborer presenting with eosinophilic meningitis and intracranial hemorrhage - Min-Nan Hung; Han-Wei Huang; Paron Dekumyoy; Wallop Pakdee; Yeong-Sheng Lee; Dar-Der Ji (Journal of the Formosan Medical Association, 2015)
We report a case of neurognathostomiasis in a Thai laborer for the first time in Taiwan. For patients with eosinophilic meningitis, neurognathostomiasis should be considered when brain image discloses subarachnoid or intracranial hemorrhage and when an appropriate exposure risk is available, especially a history of raw freshwater fish consumption in endemic areas, even a long time ago.